(3QSGdI aj EKHGJ hGLH GdhLhOs - (3YKeGf Hf SfO GdfLOj GdHUQj, HOQ GdOjf, GHf SfO , J (B1242 (3g` s
(3ChdgG (B:s
(3hHYO agPg fHPg ef GdMbGFb hRHOI ef GdObGFb ajg faGFS GdeWGdH GdYGdjI s
(3BNQgG (B:s
(3hjchf ghjI cd efgeG hhLhOg GdNGU Hg Yjf PGJg Ydi fMI eG jbhdhf Ydi JbOjQ GdhMOI hbO jSJOd Ydi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B367s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdeLGejYs